SURVEY AKTIVITAS FISIK, POLA MAKAN DAN STATUS GIZI SISWA SDN 37 MATARAM TAHUN 2023 - Simanjuntak, Gabriel Devi Manggar Ningtias; Bausad, Andi Anshari; Sukarman, Sukarman (Jurnal Ilmiah Global Education, 2023)
School age is the childhood period that lasts from six to twelve years of age. During school-age children they display individual differences in everyday life such as differences in intelligence, cognitive ability, language, personality development and physical development. What needs to be considered at this time is the child's daily physical activity and the child's eating habits at school which are carried out unintentionally can affect children's nutrition. This research is a survey research with a quantitative descriptive design conducted at SDN 37 Mataram with a sample size of 51 students. Data collection included physical activity, eating patterns, and nutritional status using a questionnaire as an instrument. Data were analyzed descriptively. The results showed that most of the students had a low physical activity category, namely 34 (55.7%), in the diet students had a good category, namely 41 (80.4%), while in the nutritional status students had a thin category, namely 43 ( 84.3%), and there was no effect between physical activity and diet and nutritional status.